Competition, Innovation, and Antitrust A Theory of Market Leaders and Its Policy Implications - Etro, Federico (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Competition, Innovation, and Antitrust develops a theory of market leadership in the presence of endogenous entry of firms and applies it to models of competition in the market and for the market. On this basis, the author provides a new approach to antitrust policy which is in support of the Chicago school but founded on a solid game-theoretic framework. The analysis is applied to the study of market leadership in the New Economy and of the recent antitrust cases involving Microsoft. Federico Etro is Associate Professor of Economics at the University of Milan, Bicocca, and President of the International Think-tank on Innovation and Competition. He has publications on leading international journals as The American Economic Review, The RAND Journal of Economics, The Economic Journal and others, and is a consultant for international organizations and companies on industrial and antitrust policy. This book explores the role of leadership in the economic theory of oligopoly, both for static oligopoly and for dynamic patent races. I thoroughly enjoyed its refreshing perspective. Simon Anderson, University of Virginia The simple but fundamental result on aggressive pricing by leaders facing endogenous entry, which has eluded researchers on the foundations of industrial organization so far, is bound to have a significant impact on the way people think about market entry, the role of potential competition, and issues of timing, strategic commitment and incumbency. Rabah Amir, University of Arizona In this innovative and thoughtful book, Etro provides a novel approach to competition policy in innovative industries. Building on the notion of Stackelberg equilibrium with endogenous entry, which he has himself contributed to develop, he highlights the crucial role of potential competition in determining market performance. It will be of great value to scholars and visionary practitioners, and may hopefully have a large impact on competition policy. Vincenzo Denicolò, University of Bologna .